Refleksi Yuridis Perkembangan Demokrasitisasi Politik Pemilu Pasca Reformasi - Bagus Anwar Hidayatulloh (UIN Sunan Kalijaga Yogyakarta, 2013)
Development of democracy in Indonesia is experiencing significant growth,especially in the time of the Reformation. Awareness of the state of democracy in Indonesia is characterized by changes in the amended constitution and also theemergence of laws and other regulations over a democracy. One of the rules and regulations are constantly changing is about elections. Election is one of thecharacteristics of countries that embrace democratic system. In the post-Reformation has happened 3 times elections, namely in 1999, 2004 and 2009. At the third electionlaws have different anyway. Because there is a political configuration that houses the elections. The election of these three would be a reflection of this nation about thedevelopment of democracy. This paper will present the existing political demokrasti tripon Election Post-Reformation, as a reflection of legal developments democratic election.